IRF3 and IRF8 Regulate NF-κB Signaling by Targeting MyD88 in Teleost Fish - Yan, Xiaolong; Zhao, Xueyan; Huo, Ruixuan; Xu, Tianjun (Frontiers in Immunology, 2020)
MyD88 is a conserved intracellular adaptor, which plays an important role in the innate immune system. MyD88 transmits signals for downstream of Toll-like and IL-1 receptors to activate NF-κB signaling pathway, which is tightly controlled in the immune response to maintain immune intensity and immune homeostasis at different stages. NF-κB signaling pathway has been extensively studied in mammals, but regulatory molecular mechanism is still unclear in teleost fish. We determined that IRF3 and IRF8 can regulate MyD88-mediated NF-κB signaling pathway in fish. Interestingly, MyD88 is precisely regulated by IRF3 and IRF8 through the same mechanism but in completely opposite ways. IRF3 promotes MyD88-mediated NF-κB signaling pathway, whereas IRF8 inhibits the signaling pathway. MyD88 is regulated via ubiquitin-proteasome degradation, whereas IRF3 or IRF8 inhibited or promoted MyD88 degradation in this pathway. Specifically, in the early stage of LPS stimulation or Vibrio infection, up-regulation of IRF3 and down-regulation of IRF8 eventually increased MyD88 expression to activate the NF-κB signaling pathway to trigger immune response. In the late stage of stimulation, down-regulated IRF3 and up-regulated IRF8 synergistically regulate the expression of MyD88 to a normal level, thus maintaining the immune balance of homeostasis and preventing serious damage from persistent over-immunization. This study presents information on Myd88-NF-κB signaling pathway in teleost fish and provides new insights into its regulatory mechanism in fish immune system.